Dissolution method for delapril and manidipine combination tablets based on an absorption profile of manidipine - Vítor Todeschini; Maximiliano S. Sangoi; Gustavo K. Goelzer; Jaison C. Machado; Clésio S. Paim; Bibiana V. Araujo; Nadia M. Volpato (Elsevier, 2016)
The present study describes the development and validation of a dissolution method for delapril (DEL) and manidipine (MAN) combination tablets, using a simulated absorption profile based on in vivo data for MAN. The suitable in vitro dissolution profile for this formulation was obtained using 900 mL of citrate buffer pH 3.2 at 37 °C±0.5 °C as dissolution medium and USP apparatus 2 (paddle) at 75 rpm. All samples were analyzed by a liquid chromatography (LC) method. Under these conditions, a significant linear relationship between the absorbed (calculated by deconvolution approach) and dissolved fractions of MAN was obtained (R=0.997) and an in vivo-in vitro (IVIV) correlation for this particular formulation containing MAN can be established. Validation parameters for dissolution methodology such as the specificity, linearity, accuracy and precision were also evaluated according to the international guidelines, giving results within the acceptable range. Therefore, the proposed dissolution conditions can be applied for the simultaneous release analysis of DEL and MAN from the solid dosage form, contributing to the improvement of the quality control of pharmaceutics and minimizing the number of bioavailability studies.